2014
DOI: 10.1371/journal.pone.0094936
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality, Bullying and Other Conduct and Mental Health Correlates of Traumatic Brain Injury in Adolescents

Abstract: ObjectiveOur knowledge on the adverse correlates of traumatic brain injuries (TBI), including non-hospitalized cases, among adolescents is limited to case studies. We report lifetime TBI and adverse mental health and conduct behaviours associated with TBI among adolescents from a population-based sample in Ontario.Method and FindingsData were derived from 4,685 surveys administered to adolescents in grades 7 through 12 as part of the 2011 population-based cross-sectional Ontario Student Drug Use and Health Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 30 publications
2
77
0
1
Order By: Relevance
“…[78][79][80] Past studies have suggested that a concussion can cause lasting defi cits through changes in physiology (e.g., disrupted serotonin pathways), mood (e.g., posttraumatic stress disorder) or behaviour (e.g., disinhibition with impulsivity). [81][82][83][84] Cognitive dissonance could also lead patients and clinicians to attribute injuries after weekend recreation to misadventure, whereas injuries following weekday occupation might be attributed to the employer. [85][86][87] With hindsight, a difference in activity restriction or cognitive dissonance might arise if the injury event was self-initiated.…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80] Past studies have suggested that a concussion can cause lasting defi cits through changes in physiology (e.g., disrupted serotonin pathways), mood (e.g., posttraumatic stress disorder) or behaviour (e.g., disinhibition with impulsivity). [81][82][83][84] Cognitive dissonance could also lead patients and clinicians to attribute injuries after weekend recreation to misadventure, whereas injuries following weekday occupation might be attributed to the employer. [85][86][87] With hindsight, a difference in activity restriction or cognitive dissonance might arise if the injury event was self-initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar questions assessing TBI have been previously validated. 10,11,18,20 Whereas respondents were normal adults, able to participate in regular adult activities, we cannot rule out the possibility of cognitive impairments affecting responses of TBI-injured adults. Of relevance here, we found that TBI adults were no more likely than non-TBI adults to assess questionnaire difficulty as ''difficult'' (10 …”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…[4][5][6] Over the past 15 years, the incidence of TBI has increased rapidly in the industrialized world, especially among youth. [7][8][9][10][11][12][13][14] In 1991, it was estimated that 1.7 million people experienced TBI in the United States. 1 By 2009, the Centers for Disease Control and Prevention (CDC) stated that TBI has become a ''silent epidemic,'' reporting an estimated 2.4 million TBI injuries captured through emergency department records, hospitalizations, or deaths in the United States, with children, adolescents, and older adults being the most likely age groups to sustain a TBI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations